LITERASI LINGKUNGAN (PENGELOLAAN SAMPAH) DENGAN METODE AMBIL, PILAH DAN KURANGI (APIK) PADA JENJANG PENDIDIKAN DASAR DI PULAU MOROTAI - Idrus, Sukarmin; Sarapung, Risky Richlos; Kusman, M Reza; Nurdin, Hayun; Fanani, Fathur Afrizal; Pina, Umi Kalsum; Ramdani, Ramdani (Jurnal Abdi Insani, 2025)
Knowledge about types of waste, waste sorting and its dangers is initial knowledge that must be possessed from an early age. This initial knowledge is part of environmental literacy. School is the most basic level of formal education in Indonesia. So indirectly, character formation about understanding waste management must be given at this level. The application of the principle of waste management, namely 3R, needs to be simplified into APiK (Take, Sort and Reduce). The purpose of implementing this method is to reduce the amount of unsorted waste in the school, thereby reducing the burden on waste officers and the accumulation of waste in the TPA. The training method in this service starts from Socialization, implementation of pre-test, screening of Apik method videos, Practice of making Waste Reduction Products and ending with a post-test. This service was carried out in an elementary education environment with 23 students participating. The entire series of activities have been carried out. Socialization and training were successfully implemented and there was an increase in student knowledge regarding waste management. They have learned how to make vermycompos, styrofoam bricks and Ecobricks. When the post-test was conducted, there was an increase to 81% of students who had understood waste management. This activity was carried out according to plan and succeeded in increasing student knowledge.